PENGARUH DEMOGRAFI, DAN LITERASI KEUANGAN TERHADAP PERILAKU MENABUNG MASYARAKAT DI KABUPATEN SIDOARJO - LATHIF UBAIDILLAH, HISYAM; ASANDIMITRA HARYONO, NADIA (Jurnal Ilmu Manajemen (JIM), 2018)
Savings is one of the important instruments in the development of Indonesia, due to the economic growth of a country can be measured from the level of investment and savings society. This research aims to analyze the effect between gender, age, number of dependents, education, income, marital status and financial literacy against saving behavior. This type of research is a research kuanlitatif by the number of samples as much as 220 respondents. The object of this research is a community in the District of Sidoarjo. Data analysis technique used was multiple linear regression analysis and using IBM SPSS version 24. The results obtained indicate that gender has no effect because male and female have the same opportunities and capabilities in owning income, age has no effect because the young or old someone will still be concerned with saving for the future, education has no effect because the high or low level of education will not membengaruhi someones savings, the number of dependents have no effect because it has had children or not, someone will save money for the future, revenue has no effect because the higher a persons income then the desire to shop is getting bigger, marital status has no effect because the married or not yet someone still will do the saving for future needs, While the financial literacy to saving behavior. Keywords: education, income, marital status, financial literacy, and saving behavior